Hemiplegic Migraine Associated With PRRT2 Variations: A Clinical and Genetic Study. (4th January 2022) - Riant, Florence; Roos, Caroline; Roubertie, Agathe; Barbance, Cécile; Hadjadj, Jessica; Auvin, Stéphane; Baille, Guillaume; Beltramone, Marion; Boulanger, Cécile; Cahn, Alice; Cata, Florina; Cheuret, Emmanuel; et al.
Abstract : Background and Objective: PRRT2 variants have been reported in a few cases of patients with hemiplegic migraine. To clarify the role of PRRT2 in familial hemiplegic migraine, we studied this gene in a large cohort of affected probands. Methods: PRRT2 was analyzed in 860 probands with hemiplegic migraine, and PRRT2 variations were identified in 30 probands. Genotyping of relatives identified a total of 49 persons with variations whose clinical manifestations were detailed. Results: PRRT2 variations were found in 12 of 163 probands who previously tested negative for CACNA1A, ATP1A2, and SCN1A variations and in 18 of 697 consecutive probands screened simultaneously on the 4 genes. In this second group, pathogenic variants were found in 105 individuals, mostly in ATP1A2 (42%), followed by CACNA1A (26%), PRRT2 ( 17%), and SCN1A (15%). The PRRT2 variations included 7 distinct variants, 5 of which have already been described in persons with paroxysmal kinesigenic dyskinesia and 2 new variants. Eight probands had a deletion of the whole PRRT2 gene. Among the 49 patients with variations in PRRT2, 26 had pure hemiplegic migraine and 16 had hemiplegic migraine associated with another manifestation: epilepsy (8), learning disabilities (5), hypersomnia (4), or abnormal movement (3). Three patients had epilepsy without migraine: 2 had paroxysmal kinesigenic dyskinesia without migraine, and 1 was asymptomatic. Discussion: PRRT2 should be regarded as the fourth autosomal dominant gene for hemiplegic migraine and screened in any affected patient, together with the 3 other main genes. Further studies are needed to understand how the same loss-of-function PRRT2 variations can lead to a wide range of neurologic phenotypes, including paroxysmal movement disorder, epilepsy, learning disabilities, sleep disorder, and hemiplegic migraine.